Bollywood : the films! the songs! the stars! - Dasgupta, Arpita; Ausaja, S. M. M.; Bachchan, Amitabh, 1942- (Dorling Kindersley limited, 2017)
I abhor the title of this book. The Indian Film Industry is what I shall always refer to as Cinema in India. We are an independent crative industry and not a derivative; any attempt to imply otherwise, shall not find favour with me...